﻿Acute toxicity test nanoherbal mahkota dewa fruit (Phaleria macrocarpa) - Leo Jumadi Simanjuntak; Cheryl Grace Pratiwi Rumahorbo (Pensoft Publishers, 2022)
A common plant from Papua, Indonesia, called Phaleria macrocarpa (mahkota dewa), has potent therapeutic components. The aim of this study was to evaluate the toxicity level of nanoherbal mahkota dewa and its effect on the changes in hematology, biochemistry, electrolytes, and histopathology of the organ. High Energy Milling (HEM) was used to produce nanoherbal mahkota dewa. LD50 was determined in three stages: dose orientation test (12 mice), preliminary test (20 mice), and LD50 determination (30 mice) for 14 days using the Thomson Weil formula. LC50 was determined using the Brine Shrimp Lethality Test method with concentrations of 1, 10, 100, 1000, and 10,000 ppm. This study revealed that the LD50 value was 1g/kg BW 0,075 and the LC50 value was 2145,0407 ppm. The nanoherbal mahkota dewa affected the histological organs, hematological, biochemical, and electrolyte parameters but did not affect the weight of the organ significantly. From this study, it can be concluded that nanoherbal mahkota dewa belongs to the category of moderate toxicity. In a proper dose, it could be processed as an herbal medicine in the future.